Розробка веб-застосунку «дошка оголошень» - Іващенко, А. О. (ХНУРЕ, 2025)
This work is devoted to the development of a classified ads web applicationwith user marketing behavior research. Its main goal is to design and deliver an intuitive, secure marketplace that connects buyers and sellers using modern, scalable, and reliable technologies. Through an analysis of sellers’ and buyers’ behavior, the work highlights factors shaping user decisions, emphasizing transparent communication, trust, and user-friendly design. Key features include catalogue, integrated payments, real-time chat, product tracking, and robust authentication. The project ultimately aims to propose a comprehensive solution that enhances the user experience and streamlines the buying and selling process for all stakeholders involved.
Keywords: оголошення; веб-застосунок «дошка оголошень»